THE ROLE OF TUTORS ON STUDENT ACTIVITY IN SMALL GROUP DISCUSSION - Yeni Rusyani; Putri Kusumawati Priyono (Jurnal Keperawatan Respati Yogyakarta, 2023)
The role of tutors in PBL is to identify student abilities, create challenges, become models, activate students, monitor student progress, and evaluate learning outcomes. The role of the tutor is one of the determining factors to make students active in group discussions. This riset to determine the effect of the role of the tutor on student activity in small group discussions. This study used a Quasy experimental design, One Group post-test only design approach. The sampling technique used is total sampling. The total research respondents were 185 students. Analysis of the data used is the Kolmogorov Smirnov test. The results showed that most of the students assessed that the tutor's role was in a Good category as many as 135 students (72.98%). Most of the students' activeness in the Small Group Discussion assessed the good category as 157 students (84.86%). There is an effect of the tutor's role with a sig value of 0.000 <0.05 and the tutor's role has an influence on student activity in Small Group Discussions with an R-value of 0.564. There is an influence of the tutor's role on student activity in Small Group Discussions.